Breaking the Cycle? Education and the Intergenerational Transmission of Violence - Erten, Bilge; Keskin, Pinar (The Review of Economics and Statistics, 2020)
We estimate the causal effects of education on the intergenerational transmission of violence against children by exploiting an extension of compulsory schooling in Turkey. Using a regression-discontinuity design, we find that the reform increased maternal education by one year, with stronger effects for women raised in rural areas. The increase in education among rural women led to a reduction in the perpetration of child physical abuse but only by mothers who were physically abused by their own families during childhood. Exploring potential channels, we document that these women were also more likely to experience improved mental health outcomes.